2020
DOI: 10.1242/jeb.228064
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of temperature and water availability on pregnancy in a viviparous lizard

Abstract: One of the greatest current threats to biodiversity is climate change. However, understanding of organismal responses to fluctuations in temperature and water availability is currently lacking, especially during fundamental life-history stages such as reproduction. To further explore how temperature and water availability impact maternal physiology and reproductive output, we used the viviparous form of the European common lizard (Zootoca vivipara) in a two-by-two factorial design manipulating both hydric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 108 publications
(113 reference statements)
0
10
0
Order By: Relevance
“…Second, all females experienced muscle loss during the experiment and losses were highest in females in dry conditions, especially if they had limited access to preferred temperatures during the daytime. Muscle wasting during pregnancy is common in reptiles (Lourdais et al 2004, 2013, Lorioux et al 2016) and skeletal muscle has been shown to be an important substrate for the reallocation of hydric resources when demands are high and intake is limited (Brusch et al 2019, 2020, Dezetter et al 2021). Because proteins are a much lower energetic source compared to lipids and their oxidation provides five times more water (Jenni and Jenni‐Eiermann 1998), increased muscle catabolism likely supported the hydric costs of reproduction in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, all females experienced muscle loss during the experiment and losses were highest in females in dry conditions, especially if they had limited access to preferred temperatures during the daytime. Muscle wasting during pregnancy is common in reptiles (Lourdais et al 2004, 2013, Lorioux et al 2016) and skeletal muscle has been shown to be an important substrate for the reallocation of hydric resources when demands are high and intake is limited (Brusch et al 2019, 2020, Dezetter et al 2021). Because proteins are a much lower energetic source compared to lipids and their oxidation provides five times more water (Jenni and Jenni‐Eiermann 1998), increased muscle catabolism likely supported the hydric costs of reproduction in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As intermediates on the capital-income breeding spectrum, Z. vivipara can accumulate vast lipid reserves after parturition, prior to hibernation (Avery 1975), but are also able to assimilate nutrients during pregnancy (Bleu et al 2013). Previous studies have found that higher temperatures, compounded by dehydration, reduce tail reserves in gestating lizards (Brusch et al 2020). Our results align with this and further suggest a potential tradeoff between tail reserves and fecundity, where larger female with small litter size are able to assimilate and invest nutrients into tail reserves but only if water is readily available (Fig.…”
Section: Water Restrictions Affect Allocation Of Resources But Not Re...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, researchers may also specify when ectoparasites are forcibly removed and animals have been exposed to an anti‐parasite treatment or spray prior to experiments. For example, Brusch et al (2020) used an anti‐parasite spray (Frontline, Merial Inc.) on European lizards Zootoca vivipara and removed visible parasites using forceps. A treatment upon arrival in the laboratory is another efficient option.…”
Section: Introductionmentioning
confidence: 99%